Sequence and conformation effects on ionization potential and charge distribution of homo-nucleobase stacks using M06-2X hybrid density functional theory calculations - Rooman, Marianne; Wintjens, René (Journal of biomolecular structure & dynamics, 2014)
DNA is subject to oxidative damage due to radiation or by-products of cellular metabolism, thereby creating electron holes that migrate along the DNA stacks. A systematic computational analysis of the dependence of the electronic properties of nucleobase stacks on sequence and conformation was performed here, on the basis of single- and double-stranded homo-nucleobase stacks of 1-10 bases or 1-8 base pairs in standard A-, B-, and Z-conformation. First, several levels of theory were tested for calculating the vertical ionization potentials of individual nucleobases; the M06-2X/6-31G ∗ hybrid density functional theory method was selected by comparison with experimental data. Next, the vertical ionization potential, and the Mulliken charge and spin density distributions were calculated and considered on all nucleobase stacks. We found that (1) the ionization potential decreases with the number of bases, the lowest being reached by Gua≡Cyt tracts; (2) the association of two single strands into a double-stranded tract lowers the ionization potential significantly (3) differences in ionization potential due to sequence variation are roughly three times larger than those due to conformational modifications. The charge and spin density distributions were found (1) to be located toward the 5′-end for single-stranded Gua-stacks and toward the 3′-end for Cyt-stacks and basically delocalized over all bases for Ade- and Thy-stacks; (2) the association into double-stranded tracts empties the Cyt- and Thy-strands of most of the charge and all the spin density and concentrates them on the Gua- and Ade-strands. The possible biological implications of these results for transcription are discussed.